An application to promote emotional skills in children with autism spectrum disorders - Azevedo, José (2018)
This paper presents an approach regarding the use of a serious game with a playware object to improve the development of emotional skills in children with Autism Spectrum Disorder (ASD). The playware object is an interactive way for the user to play the game. It acts as the game controller, has six buttons, each displaying an emoji with a different facial expression, and communicates wirelessly with the android device through Bluetooth. For this purpose, the six facial expressions tested are happiness, sadness, fear, anger, surprise and a neutral/normal, which were implemented in three different game activities: imitation, recognition, and storytelling. The avatars used in the game to represent these facial expressions were first validated through an on-line questionnaire (with 114 answers) with a mean success rate of 96.2%. In order to assess the usability of the game and the playware object, a test was performed with six typically developing children, with 94.4% answer accuracy. At last, the recognition activity was tested with six children with ASD during three/four sessions. Due to the small group test and the short number of sessions, the goal was to test the acceptance of the game rather than the users’ improvement in the activity. It is worth referring that both the serious game and the playware object had a high level of approval from the children and they expressed their interest during the activities. With this preliminary study its intended to contribute to the development of pedagogical resources to be used by professionals and families in the support of children with ASD.